Art‐based mindfulness at school: A culturally responsive approach to school mental health. Issue 10 (3rd February 2022) - Jones, Janine M.; Lee, Lisa H.
Abstract: As schools are increasingly tasked with improving student outcomes related to both academic and social and emotional wellbeing, digital interventions are becoming utilized as viable tools for successful outcomes. This study aimed to measure the effectiveness of a culturally responsive, art‐based mindfulness intervention called L.A.U.G.H.® (Let Art Unleash Great Happiness), in a diverse sample of 243 elementary school students. Using an iPad app, students practiced mindful breathing and created digital art in their classrooms. The app also measured students' moods, school connectedness, and joy of learning. The study design was a one‐group repeated measure intervention design where ratings were compared between Weeks 1, 4, 8, and 12 of the intervention. Results indicated that L.A.U.G.H.® time improved and increased students' moods, School Connectedness, and Joy of Learning over time. Race played a significant role in how students rated their feelings about school, with significant effects that emerged among Black/African American and Asian American/Pacific Islander students. Both groups began with the lowest ratings of school connectedness and demonstrated significant improvements by Week 8. This study revealed results from a digital mindfulness intervention and highlighted the importance of a nuanced study of differential impacts of such interventions among diverse students. Research Highlights: L.A.U.G.H.® (Let Art Unleash Great Happiness) time increased students' moods, School Connectedness, and Joy of Learning over time. Black students and Asian students began with significantly lower ratings of school connectedness that increased significantly through 8 weeks.